Retail Investment Financing Via Remote Digital Computer Algorithm - Matytsin, Denis (Legal Concept = Pravovaya Paradigma, 2021)
Introduction: in the paper, the author examines the activities of the Russian legislators on the formation of the legal regulation of the investment segment of the economy in order to identify their mistakes and shortcomings, as well as to justify the recommendations for fixing viable legal structures in the legislation. Such legitimate structures could be used by a wide range of individual investors-individuals – as part of their decision to diversify monetary investments in order to increase household savings for a period of 1 year or more. Methodology: the digital computer algorithms of inter-network interaction for placement and attraction of investments, their speed and independence from distance are perceived by entrepreneurs with great hope for success and attract more and more attention from investors. According to the author of the paper, by 2024, the financial digital technologies can replace up to 38% of traditional banking and payment transactions, up to 32% of insurance transactions, transactions for financing foreign trade transactions, and transactions for asset management. Based on the materialist worldview, the universal method of historical materialism, the author used the general scientific and specific scientific methods for the study, which made it possible to implement a systematic approach to the subject of research. The general scientific methods of cognition are applied: the dialectical, hypothetical-deductive methods, generalization, induction and deduction, analysis and synthesis, empirical description. The research also uses the specific scientific methods: dogmatic, comparative-legal, hermeneutic, structural-functional, etc. The scientific development of the material is carried out on the basis of a set of normative and doctrinal sources. The paper uses the federal laws and other normative acts of the Russian Federation. Federal Law No. 259-FZ of August 2, 2019 “On Attracting Investments Using Investment Platforms and on Amendments to Certain Legislative Acts of the Russian Federation”, Draft Federal Law No. 419090-7 “On Alternative Methods of Attracting Investments (Crowdfunding)”, and certain provisions of the Civil Code of the Russian Federation were studied. Draft Law No. 419059-7 “On Digital Financial Assets” of March 20, 2018, and Federal Law No. 34-FZ of March 18, 2019 “On Amendments to Parts One, Two, and Article 1124 of Part Three of the Civil Code of the Russian Federation” were critically analyzed. The doctrinal sources are represented by the scientific publications of the Russian legal scholars and economists, including: A.O. Inshakova, A.E. Kalinina, A.I. Goncharov, M.V. Goncharova, O.P. Kazachenok, E.E. Frolova, etc. Results: the Internet investing provides an opportunity to obtain funding for the implementation of a publicly announced project relatively quickly and without bureaucratization. The absence of the geographical and distance restrictions is a special advantage of investing on the Internet platforms, compared to other tools for raising capital from a wide range of investors, including individuals. This remote Internet algorithm for retail investment financing allows you to attract capital at a price that corresponds to the profitability of projects and, as a rule, is lower than the average bank interest rate for a loan. Conclusions: the conclusions and assessments on the content of the new Russian legislation are formulated. Based on the critical analysis of the scientific works of the economists and lawyers, the authors formulate the definitions of a special algorithm for remote investments from a wide range of subjects, as well as the tools for remote interaction of investors and investment organizers in the Internet space of modern Russia.